Association between sugar-sweetened beverage consumption and childhood overweight and obesity: a cross-sectional study in Beijing, China - Li, Yiran; Meng, Lulu; Zhang, Yan; Li, Wenjia; Liang, Siyu; Zheng, Jiarui; Li, Jie; Cao, Ruoxiang; Duan, Jiali; Huang, Liyu (Frontiers in Nutrition, 2025)
BackgroundThe consumption of sugar-sweetened beverage (SSB) has significantly increased and is regarded as a potential cause of overweight and obesity in children and adolescents. This study explores the association between SSB consumption and overweight/obesity among primary and secondary school students in Beijing in 2024.MethodsA total of 3,402 participants were included in this cross-sectional study conducted from October to November 2024. Binary logistic regression is used to assess the association between SSB consumption and weight/obesity.ResultsApproximately 38.5% of the study population were overweight/obese. After adjusting for covariates, SSB consumption was associated with overweight /obesity. Participants with” SSB consumption frequency ≥7 times/week” had a higher prevalence of overweight/obesity compared to participants” SSB consumption frequency < once/week” (OR = 1.396, 95%CI = 1.093–1.782). Participants with” SSB consumption quantity ≥500 mL/day” had a higher prevalence of overweight/obesity compared to those with “SSB consumption quantity <150 mL/day” (OR = 1.316, 95%CI = 1.093–1.586). Moreover, when subgroup analyses were conducted, the association between SSB consumption and overweight/obesity was more susceptible among females, younger students, and urban residents.ConclusionThe consumption rate of sugar-sweetened beverages among school-age children in Beijing is high. Student sugar-sweetened beverage consumption was significantly associated with overweight/obesity. Therefore, targeted actions and plans should be taken to reduce the consumption of SSB and control childhood obesity.